A Case Report of Locked-in Syndrome Due to Bilateral Vertebral Artery Dissection After Cervical Spine Manipulation Treated by Arterial Embolectomy. Issue 5 (February 2016) - Ke, Jiang-Qiong; Yin, Bo; Fu, Fang-Wang; Shao, Sheng-Min; Lin, Yan; Dong, Qi-Qiang; Wang, Xiao-Tong; Zheng, Guo-Qing
Abstract : Abstract: Cervical spine manipulation (CSM) is a commonly spinal manipulative therapies for the relief of cervical spine-related conditions worldwide, but its use remains controversial. CSM may carry the potential for serious neurovascular complications, primarily due to vertebral artery dissection (VAD) and subsequent vertebrobasilar stroke. Here, we reported a rare case of locked-in syndrome (LIS) due to bilaterial VAD after CSM treated by arterial embolectomy. A 36-year-old right-handed man was admitted to our hospital with numbness and weakness of limbs after treating with CSM for neck for half an hour. Gradually, although the patient remained conscious, he could not speak but could communicate with the surrounding by blinking or moving his eyes, and turned to complete quadriplegia, complete facial and bulbar palsy, dyspnea at 4 hours after admission. He was diagnosed with LIS. Then, the patient was received cervical and brain computed tomography angiography that showed bilateral VAD. Aortocranial digital subtraction angiography showed vertebrobasilar thrombosis, blocking left vertebral artery, and stenosis of right vertebral artery. The patient was treated by using emergency arterial embolectomy and followed by antiplatelet therapy and supportive therapy in the intensive care unit and a general ward. Twenty-seven days later, the patient's physical function gradually improved and discharged but still left neurological deficit with muscle strength grade 3/5 and hyperreflexia of limbs. Our findings suggested that CSM might have potential severe side-effect like LIS due to bilaterial VAD, and arterial embolectomy is an important treatment choice. The practitioner must be aware of this complication and should give the patients informed consent to CSM, although not all stroke cases temporally related to SCM have pre-existing craniocervical artery dissection.